2006
DOI: 10.1002/smll.200500244
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous Platinum Nanoparticles

Abstract: Playing the platinum card: By means of a self‐organization process at low temperature in organic solvent, porous platinum nanoparticles of excellent dispersity have been prepared. The particles are obtained as flowerlike arrays (see TEM image), and their porosity was shown to be similar to other mesoporous Pt systems. The catalytic activity of the nanoparticles is shown to be ≈60 % greater than a commercial Pt catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
199
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(210 citation statements)
references
References 30 publications
7
199
1
3
Order By: Relevance
“…We also extended the mechanistic understanding of surface diffusion to the synthesis of Pd-Pt bimetallic nanocrystals. Platinum (Pt) is an invaluable material due to its excellent performance as catalysts in a myriad of industrial processes (21)(22)(23)(24)(25). However, Pt is extremely expensive due to its low content in the Earth's crust and the continuous growth of demand in the automobile industry.…”
Section: Resultsmentioning
confidence: 99%
“…We also extended the mechanistic understanding of surface diffusion to the synthesis of Pd-Pt bimetallic nanocrystals. Platinum (Pt) is an invaluable material due to its excellent performance as catalysts in a myriad of industrial processes (21)(22)(23)(24)(25). However, Pt is extremely expensive due to its low content in the Earth's crust and the continuous growth of demand in the automobile industry.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Pores increase the surface area-to-volume ratio of the NSs, since a greater fraction of atoms is located at the surface and leads to increased chemical reactivity of the NSs (36). We decided to test the chemical reactivity of the TeNSs as an antibacterial agent since it was recently shown that chemically synthesized tellurium NSs showed very promising antibacterial properties against E. coli, comparable to or higher than those to silver NSs (14).…”
Section: Discussionmentioning
confidence: 99%
“…the (111) , (200) , (200) and (311) planes [15]. Although several solution preparation of Pt° nanoparticles have been reported [14][15][16][17][18][19][20][21][22][23][24][25][26][27] no solid state methods for to prepare Pt° nanoparticles are available. The first way, solution methods, in spite of that to allow the size and morphology control, their incorporation to a solid state device could be not easy.…”
Section: Resultsmentioning
confidence: 99%
“…Also Nanoporous or mesoporous Platinum has been especially useful in these applications [26]. However, the methods of preparation of porous Pt are scarce.…”
Section: Introductionmentioning
confidence: 99%